Sticking, steering, squeezing and shearing: cell movements driven by heterotypic mechanical forces. (October 2018) - Labernadie, Anna; Trepat, Xavier
Abstract : During development, the immune response and cancer, cells of different types interact mechanically. Here we review how such heterotypic mechanical interactions enable cell movements. We begin by analyzing the heterotypic forces that single cells use to adhere and squeeze through tight barriers, as in the case of leucocyte extravasation and cancer metastasis. We next focus on the different mechanisms by which adjacent tissues influence each other's movements, with particular emphasis on dragging forces during dorsal closure in Drosophila and shearing forces during gastrulation in zebrafish. Finally, we discuss the mechanotransduction feedback loops that enable different cell types to steer each other's migration during development and cancer. We illustrate these migration modes focusing on the combination of attractive and repulsive cues during co-migration of neural crest cells and placodes in Xenopus, and of fibroblasts and cancer cells during invasion. Throughout the review, we discuss the nature of the heterotypic contact, which may involve both homophilic and heterophilic interactions between adhesion receptors.